A CASE OF AVASCULAR NECROSIS OF THE BILATERAL CAPUT FEMORAL IN FEMALE PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS - Femi Syahriani; Muhammad Andry Usman; Nur Fatma (Alami Journal (Alauddin Islamic Medical) Journal, 2023)
Avascular necrosis (osteonecrosis, aseptic necrosis, or ischemic necrosis) is a pathological condition caused by various etiologies that causes a decrease in vascular supply resulting in bone ischemia. Avascular necrosis increases morbidity in systemic lupus erythematosus (SLE) patients. Several contributing factors, namely the vascular supply to the bone, the use of corticosteroids, vasculitis, cyclofosfamide and SLE itself, are risk factors for avascular necrosis. We reported a case of a 20-year-old woman who came to the hospital complaining of pain in both hips, causing difficulty in walking and daily physical activities. The patient was diagnosed with SLE in 2017, and one of the therapies consumed is glucocorticoids in addition to DMARD drugs (Disease Modifying Arthritis Rheumatoid Drugs). Physical examination found a limited Range of Movement (ROM) both in bilateral flexion and extension at the hip joint. Bilateral hip joint radiography shows a necrotic avascular appearance of bilateral femoral heads. Then a total hip replacement was performed, and it underwent repair.